1998
DOI: 10.2170/jjphysiol.48.505
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Changes in the Thermogenesis of Rats by Cold Acclimation and Deacclimation.

Abstract: Male Wistar rats, aged 6 weeks, were maintained at 25 degreesC for 9 to 11 weeks (W group), at 10 degreesC for 9 to 11 weeks (C group), and at 25 degreesC for 2 weeks after exposure to 10 degreesC for 9 weeks (D group). Thermogenesis at 10 degreesC was significantly greater than at 25 degreesC. Thermogenesis per body mass in the C group was greater than in the W and D groups. The RQ value at 10 degreesC was greater than at 25 degreesC in the W group, whereas the opposite was observed in the C and D groups. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
5
16
0
Order By: Relevance
“…The growthrelated gain of body weight was significantly inhibited by cold exposure in the current study. Similar results were also reported elsewhere [2,9]. The inhibition of growth may be closely associated with the stress indicated by the atrophy of the thymus and the hypertrophy ( pϾ0.05) of adrenal observed in the cold-ex-Cold Exposure Changes Muscle Function posed rats.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The growthrelated gain of body weight was significantly inhibited by cold exposure in the current study. Similar results were also reported elsewhere [2,9]. The inhibition of growth may be closely associated with the stress indicated by the atrophy of the thymus and the hypertrophy ( pϾ0.05) of adrenal observed in the cold-ex-Cold Exposure Changes Muscle Function posed rats.…”
Section: Discussionsupporting
confidence: 88%
“…The inhibition of growth may be closely associated with the stress indicated by the atrophy of the thymus and the hypertrophy ( pϾ0.05) of adrenal observed in the cold-ex-Cold Exposure Changes Muscle Function posed rats. Hori et al [2] suggested that the lower body weight in the cold-exposed rat was caused by a greater thermoregulatory thermogenesis in a cold environment. The increased weight of brown adipose tissue also suggests the enhanced thermogenesis and metabolic rate [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, significantly elevated levels of NE in the VMH were detected in the 7D, 14D and 28D groups. Experimental observations have indicated that chronic infusion of NE into the VMH increases BAT weight (Cincotta et al, 2000), and development of BAT thermogenesis (Himms-Hagen, 1984) and masses (Hori et al, 1998) were observed after several weeks of cold exposure in rats. Thus, activation of neurons in the VMH seems to require a few weeks of cold exposure, and NE in this region may be associated with enhancement of activity of BAT thermogenesis.…”
Section: Article In Pressmentioning
confidence: 99%